(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
It is a situation where a computer programming and the information or data to be worked on is widely spread over more than one computer, typically over a network. Prior to economical computer power on the desktop, computing was actually centralized. Networking and distributed systems provide the infrastructure for computation, communication and storage involving a heterogeneous and potentially large number of people, hardware devices, and software processes. Issues of concern include performance, security, scalability, functionality, and manageability.